Detection of oprL gene and antibiotic resistance of Pseudomonas aeruginosa from aquaculture environment - Abdullahi, Rakiyah; Samuel, Lihan; Carlos, B.S; Lesley Maurice, Bilung; Kathleen, Michelle Mikal; Felecia, C. (Pelagia Research Library, 2013)
Pseudomonas aeruginosa is a gram-negative rod shape bacterium belonging to the family Pseudomonadaceae. The species is highly adaptable opportunistic pathogen, capable of surviving in a variety of environment, including aquaculture environment. Antibiotics are used in the aquaculture environment, and their improper usage poses a risk of potential transfer of resistance from aquaculture bacteria to human and animal pathogens. This study was conducted to isolate P. aeruginosa from fish, prawn and water samples, followed by PCR detection of oprL gene locus. The antibiotic resistance pattern of the isolates was also determined. Based on the results from PCR analysis performed, 13 isolates of P. aeruginosawere isolated. All of the isolates tested were resistance to at least one antibiotic. Highest level of resistance was observed against ampicillin and erythromycin while the lowest was observed against gentamicin, norfloxacin and nalidixic acid. This study suggested that the presence of the bacteria in the aquaculture environment may pose the risk of antibiotic resistance to those who are exposed to the aquaculture environment.Based on the results of this study, it can be said that gentamicin, norflaxin and nalidixic acid can be effective agents for the treatment of P. aeruginosa.